Measurement of heat, strain, and refractive index with multicore optical fibers - Güvenç Kılıç, Sema. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
In this thesis, different types of multicore optical fibers are designed and employed in the optical sensing experimental setups to investigate their detection abilities of temperature, heat transfer rate, strain, and refractive index. In the first section of this comprehensive investigation, a four-core optical fiber is introduced as a calorimetric gauge for the measurements of one-dimensional heat transfer rates. Transient heat pulses from an Nd:YAG laser are sent onto Aluminum coated surface, provided that the laser pulse is focused onto one of the optical fiber cores only. As a result of this, a phase shift in the interference pattern occurs and the corresponding optical signal is recorded by a CMOS camera. In the second section, the thermal expansion property of a stainless-steel cylinder is used to generate a strain on the optical fiber cores. Multicore fiber is coiled around a solid stainless-steel cylinder to obtain a circular optical fiber loop and this cylinder is placed onto the heater. Heating the stainless-steel cylinder results in thermal expansion in radial direction and a shear strain in the optical fiber cores. Thereby, a phase shift in the transmission spectrum is observed and monitored by the camera. As a third study, a four-core fiber is proposed and demonstrated for temperature sensing and heat transfer rate measurements. Laser heat pulses from are sent onto this Aluminum coated surface, which results in a variation in the interference pattern as a result of change in the refractive index and physical lengths of the cores. In addition to this experiment, hot air vortices were sent onto Aluminum coated surface of the fiber and variations in interference pattern are recorded. In the last section, a seven-core optical fiber with two fiber Bragg gratings is employed to detect the refractive index changes of surrounding environment. A small portion of optical fiber is etched in order to further expose the outer six cores to the surrounding environment. As the outer cores are affected by both temperature and refractive index change, the center core is only affected by the temperature.
Keywords: Optical fibers.